The Performance of Stable Zones Protocol for Heterogeneous Wireless Sensor Networks - Khedhiri, Kamel; Djabbour, Djammal; Cherif, Adnen (Engineering, Technology & Applied Science Research, 2024)
Wireless sensor networks are characterized by significant constraints, with the primary performance parameter being their lifetime. In the context of a wireless sensor network, the distance from the base station emerges as a critical factor that influences the energy consumption of the nodes, thus affecting the overall network lifetime. To address this issue, this study introduces the Stable Zones Protocol for Heterogeneous wireless sensor networks (SZP-H). This protocol strategically divides the network into distinct zones, each differing from the other in terms of its distance from the base station and the initial energy available. This protocol outperformed traditional protocols, effectively mitigating the challenges associated with node energy consumption and improving the overall performance of the wireless sensor network. The simulation results show that SZP-H achieves the highest possible stable period and lifetime and the highest throughput level compared to the FBECS, E-CAFL, and LEACH-FC protocols. Specifically, SZP-H achieves a remarkable extension of the network’s lifetime by a ratio of 303%, and 275% compared to FBECS, E-CAFL, and LEACH-FC.